Effect of Heat Treatment on the Structural Properties and Martensitic Transformation of Ni-26.5at. %Ta High Temperature Shape Memory Alloy - Yildiz, Koksal (Gazi Univ, 2020)
The effect of heat treatment at 450 degrees C, 550 degrees C and 650 degrees C temperatures for 1 hour on the structural properties and the transformation behaviour of Ni-26.5at. %Ta high temperature shape memory alloy have been examined by XRD, SEM-EDX analysis and DSC measurements. The SEM-EDX investigations showed that microstructures of all heat-treated alloy samples consisted of Ta-rich NiTa2 precipitate phase and matrix. The XRD results indicated that both numbers and intensities of martensite phase reflections of the alloy highly increased as a result of heat treatment at 650 degrees C. This was indication that the structural properties of the alloy were significantly affected by heat treatment at 650 degrees C. The thermal measurements revealed that the high temperature shape memory behaviour of the alloy did not changed with heat treatment. However, it was seen that heat treatment performed at 450 degrees(C) caused shifting martensitic transformation temperatures of the alloy and hence transformation hysteresis value of the alloy increased.
Keywords: Ni-Ta; Martensitic; Transformation; High temperature shape; Memory alloy